Entwicklung einer Betriebsstrategie zur Energierückgewinnung in hybriden Mehrverbrauchersystemen - Nagel, Philip (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2016)
Energy management strategies are developed for hybrid drive systems in which multiple actuators are interacting with an accumulator. The strategies are derived using a universal approach for efficiency assessment of control decisions. Therefore the accumulator's power flow is weighted by its impact onto the internal combustion engine. Experimental studies with a telescopic handler show up to 10% of measured fuel savings.